Mic As Weapon: Analysis Of Breaking Silence Through Feast’s Lyrics In The Context Of Educational Management - Putri, Nur Amalia; Rusmawaty, Desy; Suhatmady, Bibit (Journal of Educational Management Research, 2025)
This study examines how the Indonesian rock band .Feast uses song lyrics as a form of critical discourse to challenge social, political, and ideological structures in contemporary Indonesia. Analyzing three of their most charged songs—“Peradaban,” “Kami Belum Tentu,” and “Padi Milik Rakyat”—the research employs Critical Discourse Analysis (CDA) with Norman Fairclough’s three-dimensional model and Teun A. van Dijk’s socio-cognitive framework. The findings reveal that .Feast’s lyrics reflect societal frustrations over inequality, corruption, violence, and disillusionment, using elements like metaphor and irony to critique and resist hegemonic political narratives. The songs serve as both representations of social realities and performative interventions in public discourse. The study underscores the microphone as a metaphorical weapon against silence and marginalization, affirming the political value of popular music. It highlights the importance of analyzing music as a legitimate space for civic engagement and discourse. This research has implications for educational management by encouraging critical thinking and civic engagement in students through popular culture. Integrating music into curricula can foster discussions on power dynamics, social justice, and creative expression, empowering students to challenge societal norms and develop as informed, socially conscious individuals.